2010
DOI: 10.1002/uog.7593
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of intrapulmonary artery Doppler to improve prediction of survival in fetuses with congenital diaphragmatic hernia treated with fetal endoscopic tracheal occlusion

Abstract: Objective To evaluate the contribution of intrapulmonary artery Doppler in predicting the survival of fetuses with congenital diaphragmatic hernia (CDH) treated with fetoscopic tracheal occlusion (FETO). Methods A cohort of 41 fetuses (between 24 and 28 weeks of gestation) with CDH was treated with FETO. The observed/expected lung-to-head ratio (O/E-LHR), pulmonary artery pulsatility index (PI), peak early diastolic reversed flow (PEDRF) and peak systolic velocity (PSV) were evaluated before FETO, and their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 34 publications
1
49
0
2
Order By: Relevance
“…As increasing studies incorporate the use of fetal lung Doppler to improve the prediction of survival [6,10,11] and neonatal morbidity [8,9] in CDH fetuses, examiners should perform a sufficient number of examinations before considering incorporating these Doppler parameters into their clinical practice. Taking into account the rarity of this congenital disease and the number of scans necessary to achieve competence, this training must be performed in referral units with experienced operators in order to accelerate the learning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As increasing studies incorporate the use of fetal lung Doppler to improve the prediction of survival [6,10,11] and neonatal morbidity [8,9] in CDH fetuses, examiners should perform a sufficient number of examinations before considering incorporating these Doppler parameters into their clinical practice. Taking into account the rarity of this congenital disease and the number of scans necessary to achieve competence, this training must be performed in referral units with experienced operators in order to accelerate the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler evaluation of fetal lung circulation has been suggested as a surrogate of lung hypoplasia and intrapulmonary hypertension [2,3,4,5], allowing stratification of CDH cases with a high risk to develop severe neonatal pulmonary hypertension [6,7,8], neonatal morbidity [9] and mortality [6,10,11]. However, intrapulmonary artery Doppler evaluation is a demanding measurement in CDH fetuses due to the difficult observation and insonation of the intrapulmonay artery under a reduced lung size, and concerns exist whether the clinical application of such parameters could be influenced by the operator competences [5].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the worse the fetal pulmonary hemodynamics, the more hypoplastic are the neonatal lungs. Subsequently, a correlation between hemodynamic parameters and survival rate has been established in human fetuses with CDH (28,29).…”
Section: Effects Of To In Cdh Do Not Correlatementioning
confidence: 99%
“…Previous studies in CDH suggest that branch pulmonary artery diameter (PA d ) measurements are directly correlated with lung size - and, therefore, pulmonary hypoplasia - and predict postnatal PH [12,13]. In addition, fetal measurements of downstream pulmonary vascular resistance, such as the pulsatility index (PI), which reflects the variability of blood velocity within a vessel, and the peak early diastolic reversed flow (PEDRF), which is a component of the intrapulmonary waveform and reflects both the downstream pulmonary artery vascular resistance and discriminatory blood flow through the ductus arteriosus [14], have been shown to predict survival in subsets of patients with CDH [15,16]. Finally, a small series demonstrated that abnormal PI measured between 19 and 23 weeks' gestation was present in 6 fetuses with autopsy-proven pulmonary hypoplasia, 2 of whom had CDH [17].…”
Section: Introductionmentioning
confidence: 99%